2010
DOI: 10.1051/0004-6361/201014254
|View full text |Cite
|
Sign up to set email alerts
|

When an old star smolders

Abstract: Polycyclic aromatic hydrocarbons (PAHs) produce characteristic infrared emission bands that have been observed in a wide range of astrophysical environments, where carbonaceous material is subjected to ultraviolet (UV) radiation. Although PAHs are expected to form in carbon-rich AGB stars, they have up to now only been observed in binary systems where a hot companion provides a hard radiation field. In this letter, we present low-resolution infrared spectra of four S-type AGB stars, selected from a sample of 9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 39 publications
(48 reference statements)
6
52
0
Order By: Relevance
“…It should be noted that this dust feature has also been detected in AGB stars outside our galaxy (e.g. Lebzelter et al 2006) and in the spectra of S-type AGB stars (Smolders et al 2012).…”
Section: Consequences Of Our Measurements For the Astronomical 13 μM supporting
confidence: 59%
See 2 more Smart Citations
“…It should be noted that this dust feature has also been detected in AGB stars outside our galaxy (e.g. Lebzelter et al 2006) and in the spectra of S-type AGB stars (Smolders et al 2012).…”
Section: Consequences Of Our Measurements For the Astronomical 13 μM supporting
confidence: 59%
“…In short, the following comparisons confront normalized dust emissivities with mean residual dust emissions in the 11−15 μm range. Just for comparison, the residual emission spectrum of an S-type AGB star as seen with Spitzer -taken from Smolders et al (2012) -is also shown.…”
Section: Consequences Of Our Measurements For the Astronomical 13 μM mentioning
confidence: 99%
See 1 more Smart Citation
“…All our sources follow the trend between the effective temperature of the central star and the central wavelength of the 7-8 μm PAH feature (Sloan et al 2007;Smolders et al 2010). The carriers of the class C features are proposed to be aliphatic carbonaceous material (Sloan et al 2007).…”
Section: Pahsmentioning
confidence: 59%
“…For example, S-type stars, which are undergoing the transition from oxygen-rich to carbon-rich and thus have C/O ∼ 1, do not yet form carbon-rich dust. However, due to non-equilibrium chemistry effects carbon-rich molecules, such as PAHs, HCN, and C 2 H 2 can be seen (Hony et al 2009;Smolders et al 2010). In the carbon-rich case, the excess carbon is used to form, for example, CN, C 2 , C 2 H 2 , CH 4 , polycyclic aromatic hydrocarbons (PAHs), and SiC.…”
Section: Introductionmentioning
confidence: 99%